IMF Staff papers : Volume 28 No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1981)
The purpose of this paper is to formulate a model for developing countries that allows output, prices, international reserves, money, and government taxing and expenditure policies to be determined simultaneously. The model developed, which stresses the key role of monetary disequilibrium, is a formal representation of the theory underlying stabilization programs, including those devised by the IMF, that are implemented to combat the twin problems of inflation and an adverse balance of payments. Programs designed to achieve rapid results on the balance of payments via sharp deflation are likely to have significant and undesirable effects on output, employment, and factor incomes, particularly in the short run. Thus, the program may impose an excessive burden on a typical developing country both because incomes are already near the subsistence level and because the employment effect is likely to fall disproportionately on the fledgling industrial sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet